2019
DOI: 10.3390/en12081536
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Kalina Based Power and Cooling Cogeneration Cycle Employed Once Through Configuration

Abstract: The Kalina cycle (KC) has been considered one of the most efficient systems for harvesting low grade heat since its proposal and various modifications have been proposed. Recently, Kalina based power and cooling cogeneration cycles (KPCCCs) have attracted much attention and many studies have been conducted. In this paper, a cogeneration cycle of power and absorption refrigeration based on the Kalina cycle system 11 (KCS-11) is proposed. The cycle combines a KC and aqua-ammonia absorption refrigeration cycle (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Kalina cycle has been considered as an effective power cycles for low temperature waste heat recovery. It has many many practical advantages as compared to Rankine cycle [9,10]. A Kalina based cogeneration system of power and refrigeration showed significantly higher energy efficiency as compared to the stand-alone Kaline cycle [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kalina cycle has been considered as an effective power cycles for low temperature waste heat recovery. It has many many practical advantages as compared to Rankine cycle [9,10]. A Kalina based cogeneration system of power and refrigeration showed significantly higher energy efficiency as compared to the stand-alone Kaline cycle [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has many many practical advantages as compared to Rankine cycle [9,10]. A Kalina based cogeneration system of power and refrigeration showed significantly higher energy efficiency as compared to the stand-alone Kaline cycle [9]. Numerical study of Kalina cycle utilizing low temperature geothermal heat source at 145℃ for power generating reported a cycle efficiency of 12.95% [10].…”
Section: Introductionmentioning
confidence: 99%
“…After condensing and throttling, the high-concentration refrigerant could make the chilled water reach a lower cooling temperature, thereby improving the cooling capacity of the system. Based on the above work, Cao et al [3] added a regenerator into the CCP system and determined that the exergy efficiency of the system increased from 5.4% to 16.23% according to the optimization analysis by a genetic algorithm (NSGA-II). Hua et al [4] proposed a novel ammonia-water CCP system based on a modified Kalina cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al [15] inserted the ARC into Kalina cycle between the separator and the high-temperature recuperator to further utilize the heat contained by the ammonia-poor solution at the separator outlet. Kim et al [16] used the saturated liquid at the separator outlet as the heat source of ARC and studied the impact of the reduction of heat exchangers on the system performance by sharing the condenser between the two subsystems. The results showed that the system performance is improved without an additional heat exchanger.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems can offer improved thermal matching with sensible heat sources and sinks (such as vaporized LNG) and operational flexibility, compared with cycles using pure working fluids, and consequently lower irreversibilities, and avoid the use of ozone-depleting or global warming working fluids [11]. KC configurations particularly adapted to low-grade heat utilization include Kalina cycle system (KCS) 34 for combined power and municipal heat applications [12] and other KC variants [13]. Low-grade heat driven KC-based combined absorption power-cooling (APC) cycles, without integration with LNG regasification, have also been proposed [14].…”
Section: Introductionmentioning
confidence: 99%